ChatGPT to Foster Students’ Engagement in Writing Class: An Intervention Study - Anjarani, Shelia; Furqon , Miftahul; Rakhmawati, Fitri (VELES Voices of English Language Education Society, 2024)
Enhancing student engagement is essential for improving learning outcomes in English as a Foreign Language (EFL) writing classes. This study investigates the use of Artificial Intelligence (AI), particularly ChatGPT, to foster engagement through personalized feedback, creative expression, and interactive learning. Conducted at an Islamic university in Indonesia with 80 participants, the research employed a quasi-experimental design to assess ChatGPT’s impact on behavioral, cognitive, and emotional engagement. Participants were divided into control and experimental groups, with the latter utilizing ChatGPT for brainstorming and instructional support. The results showed significantly higher engagement levels among the experimental group across all dimensions, highlighting ChatGPT’s role in creating student-centered environments that enhance traditional teaching methods. By offering real-time, tailored assistance, ChatGPT boosts motivation and deepens cognitive and emotional connections to learning tasks. This study contributes to the growing literature on AI in education by demonstrating ChatGPT’s effectiveness in EFL writing instruction and emphasizing the need for innovative, AI-integrated pedagogical approaches to enrich learning experiences. Future research should explore the broader applications of AI in language education, addressing scalability, diverse learner needs, and long-term impacts on academic performance.